PENGUATAN ASPEK SUMBER DAYA MANUSIA DAN ORGANISASI DALAM KEBANGKITAN BISNIS PASCA PANDEMIK MELALUI FUNGSI KEPEMIMPINAN (Studi Kasus Penelitian Kualitatif pada Lembaga Keuangan Mikro Syari’ah Pekalongan) - Arif Budiharjo; Latief Z Nur; Saniyya Nabila Su’daa (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
This study aims to analyze qualitatively what happened and how Islamic microfinance institutions in Pekalongan strengthen their human and organizational aspects towards the rise of post-pandemic business through their leadership functions. The results of this study are that Islamic microfinance institutions in Pekalongan, relatively tend to be able to maintain their existence in the wave of difficulties due to the COVID-19 pandemic in 2020 and 2021 ago. And at the present time, namely 2022, they tend to try to overcome the revival to strengthen their institutions and their business capabilities through targeted movements because of the leadership function in these financial institutions. The results of this study also stated the precise strategies of Islamic microfinance institutions in Pekalongan with professionalization in terms of human resources and organizational commitment to continue to maintain their existence and development. So the implication is that there is an increasing ability in the development of both its human and organizational resources, even though the financial institution has just experienced a period of difficulty, namely during the pandemic.